Tingkat Literasi Informasi Siswa Pada Era Pembelajaran Digital: Survei Pada Sekolah Menengah Atas - Nurlia; Samaduri, Alwia; Matoneng, Theresia Andriani (Jurnal Biologi Babasal, 2025)
The low skill level of students in assessing the accuracy and credibility of information from various sources leads to the spread of misinformation and a lack of critical understanding in learning. The purpose of the study was to determine the level of information literacy of grade X high school students. This descriptive method research was conducted in the odd semester of the 2024/2025 academic year on 35 students from class X SMA Negeri 2 Luwuk. The data collection method used a questionnaire, which consisted of 25 statements and 5 indicators of information literacy. The percentage of each category was included in the quantitative descriptive analysis of the data obtained. The results showed that generally the information literacy skills of grade X students of SMA Negeri 2 Luwuk were in the good category, which amounted to 83%. This means that students are generally able to access, evaluate and use information effectively.